Analisis Tingkat Penghasilan Pensiun (TPP) Pekerja dan Faktor yang Mempengaruhinya Serta Optimalisasi Peran Dana Pensiun Swasta di Indonesia - Syarifudin Yunus (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research concludes that the Income Level (TPP) received by workers at retirement is only 10% of the last salary obtained from the mandatory pension program, a decrease in income of 90% of the last salary. The monthly living cost needs of retirees in retirement (food, monthly shopping, water costs - electricity, internet, lifestyle, health insurance, etc.) obtained data of IDR 5,600,000, - or equivalent to 56% of the last salary per month. So in actual terms, the level of retirement income (TPP) of retirees in Indonesia there is a gap of IDR 4,600,000, - or 46% less than the last salary per month. This condition causes retirees to fail to maintain their standard of living in old age, in addition to experiencing financial problems in retirement. Factors that affect the amount of a person's TPP consist of: 1) type of work, 2) pension program participated in, 3) length of service and salary amount, 4) investment return rate from the pension program, 5) government regulations, 6) macroeconomic factors and inflation, 7) health conditions of retirees, 8) family responsibilities, and 9) pension fund education determine the size of the level of retirement income. Optimizing private pension funds plays an important role in increasing TPP as a guarantee of income in retirement and creating financial independence in old age, in addition to improving quality of life. For this reason, private pension funds must be managed more optimally to achieve significant investment performance, improve pension fund literacy, target formal and informal workers, and diversify adequate products and services through digitalization of pension fund access and services to encourage significant growth in private pension fund participation.